Pendidikan Kesehatan untuk Meningkatkan Pengetahuan Masyarakat tentang Hipertensi di Padukuhan Siyono Kidul, Kalurahan Logandeng, Kapanewon Playen Kabupaten Gunung Kidul - Nur Cahyati, Agus; Amin, Ihwan; Rizqy, Miftahur; Alvina Salsabila, Alice; Maulani, Hidayah; Agustria, Maisya; Ina Masitoh, Siti; Afrilia Coel, Clarita; Khoirun Isnan, Adinda; Rahmadania Kusmawar, Annisa; Ratna Ningsih, Sri (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
Hypertension is one of the most common non-communicable diseases found in the community and is widely known as a silent killer because it often presents without symptoms until serious complications occur. The high prevalence of hypertension across various regions highlights the need for structured health promotion and prevention efforts through educational interventions. This community service program aimed to improve the knowledge of residents in Siyono Kidul Hamlet about hypertension through a health education session delivered using presentation media. A quantitative approach with a pre–post test design was employed, involving 30 participants as respondents. The activity began with a pre-test to assess baseline knowledge, followed by a health education session covering the definition, signs and symptoms, risk factors, complications, and preventive measures related to hypertension. After the session, participants completed a post-test to measure knowledge improvement. The results showed a significant increase in participants’ knowledge, with all respondents achieving a “good” category after the intervention. These findings indicate that health education incorporating lectures and visual media is effective in enhancing community health literacy. This program has important implications for hypertension prevention efforts and can serve as a model for similar community-based health interventions in other areas with comparable needs.